Lower aldosterone–renin ratio is a risk factor for total and cancer death in Japanese individuals: the Takahata study. (3rd October 2014) - Daimon, Makoto; Konta, Tsuneo; Oizumi, Toshihide; Kameda, Wataru; Susa, Shinji; Terui, Ken; Nigawara, Takeshi; Kageyama, Kazunori; Ueno, Yoshiyuki; Kubota, Isao; Yamashita, Hidetoshi; Kayama, Takamasa; et al.
Summary Objective A higher plasma aldosterone–renin ratio (ARR) is an established marker for screening for primary aldosteronism (PA). The association between higher ARR and mortality in a general population has not been fully explored. We here examined whether higher ARR is a risk factor for total and cause‐specific mortality in a Japanese population. Subjects and Methods A population‐based, longitudinal study of 1, 310 Japanese individuals (age: 63·9 ± 9·8 years) enrolled in the Takahata study between 2004 and 2006 and followed for up to 8 years. The incidence and causes of death were monitored annually until 10 January 2012 (median follow‐up: 2691 days). Results During the follow‐up period, 64 subjects died. Kaplan–Meier analysis showed a significantly increased risk for total and cancer mortality in subjects with lower ARR (log‐rank P < 0·001). Cox's proportional hazard model analyses with adjustment for age and gender showed that lower ARR was associated with increased total and cancer mortality in subjects with low (≦72) vs high (>72) ARR (hazard ratios and 95% confidential intervals: 2·56, 1·44–4·56 and 2·78, 1·16–6·65, respectively). Conclusions Lower ARR was a significant and independent risk factor for increased total and cancer mortality in this Japanese population. Subjects with higher ARR were not‐at‐risk for total death in general. These findings increase the necessity for identifying people with PA from those with higher ARR. People with higher ARR without PA may be at very low risk for total and cancer death.